PlMAPK10, a Mitogen-Activated Protein Kinase (MAPK) in Peronophythora litchii, Is Required for Mycelial Growth, Sporulation, Laccase Activity, and Plant Infection - Jiang, Liqun; Situ, Junjian; Deng, Yi Zhen; Wan, Lang; Xu, Dandan; Chen, Yubin; Xi, Pinggen; Jiang, Zide (Frontiers in Microbiology, 2018)
Mitogen-activated protein kinase (MAPK) pathways are ubiquitous and evolutionarily conserved signal transduction modules directing cellular respond to a diverse array of stimuli, in the eukaryotic organisms. In this study, PlMAPK10 was identified to encode a MAPK in Peronophythora litchii, the oomycete pathogen causing litchi downy blight disease. PlMAPK10, containing a specific and highly conserved dual phosphorylation lip sequence SEY (Serine-Glutamic-Tyrosine), represents a novel group of MAPKs as previously reported. Transcriptional profiling showed that PlMAPK10 expression was up-regulated in zoospore and cyst stages. To elucidate its function, the PlMAPK10 gene was silenced by stable transformation. PlMAPK10 silence did not impair oospore production, sporangium germination, zoospore encyst, or cyst germination but hindered hyphal growth, sporulation, pathogenicity, likely due to altering laccase activity. Over all, our results indicated that a MAPK encoded by PlMAPK10 gene in P. litchii is important for pathogenic development.